Analisis Bayesan Data DNA Flositometri - Shahran, Mohd Kidin (Universiti Putra Malaysia Press, 1995)
A newly proposed model using L function developed by Mohd. Kidin (1986, 1992) was used to estimate cell proportions in the G1-, S- and G2+M - phases of the cell cycle. Bayesian approach is proposed via a mixture of three components distribution. The method of analysis is tested on simulated data before being applied to real data.